A framework for modeling structural association among De‐Motivators of scaling agile. Issue 8 (3rd June 2021) - Abrar, Muhammad Faisal; Ali, Sikandar; Majeed, Muhammad Faran; Khan, Sohail; Khan, Muzamil; Ullah, Hamid; Khan, Mushtaq Ahmad; Baseer, Samad; Asshad, Muhammad
Abstract: Usage of agile methods for software development has increased in recent times. Rapid delivery of software products is ensured by these methods with less expense and high user gratification. Application of these methods on a large scale causes many De‐Motivators or challenges as initially these methods were aimed at those developmental teams that worked on small scale. However, no effort has been made yet to hand out the various correlations among the challenges. To fill the space, the Interpretive Structural Model (ISM) approach is used to reconnoiter the correlations among the De‐Motivators regarding Scaling Agile Software Development Methodologies (ASDM) from the management perspective. Creation of a framework for structural modeling association among the De‐Motivators is the aim of this study. To attain the goal, a hybrid methodology was applied based on a Systematic literature review (SLR), empirical survey, and ISM. First, we pointed out 15 De‐Motivators of Scaling ASDM from management perspectives through SLR study. Second, with the help of 59 experts from different countries, a questionnaire survey was conducted to empirically examine the correlations among the detected De‐Motivators. Further, correlations among the challenges are discovered with the usage of ISM through review of the panel, and they accomplish the categorization through CrossImpact Matrix Multiplication Applied Approach. Abstract : This review focuses on surgical techniques for complete surgical metastasectomy of spinal metastatic lesions, the potential indications, and the published clinical outcomes, and discusses the future prospects.